Institutional capacity building in regional policy-making for sustainable development - Khakee A. (Interdependency between agriculture and urbanization: Conflicts on sustainable use of soil and water, 2001)
Sustainable development has become a popular concept among regional and urban authorities. Originally a purely ecological concept, it has been extended to include economic and social aspects. At the same time the concept has political and ideological loading that has instigated different standpoints among policy-makers, interest organisations and other community interests. This paper has a specific aim, namely to examine how local development authorities build institutional capital for sustainable development. It does so in the context of the formulation of Agenda 21 by the city authorities in Göteborg, Sweden.
Seminar: Interdependency between Agriculture and Urbanization: Conflicts on Sustainable Use of Soil and Water, 2000/04/02-06, Tunis (Tunisia)